2011
DOI: 10.1002/nau.21052
|View full text |Cite
|
Sign up to set email alerts
|

Normal bladder sensations in healthy volunteers: A focus group investigation

Abstract: By means of focus group research it is possible to describe the development of normal bladder sensation and to refine terminology used by healthy participants. The findings show that two types of bladder sensations are reported spontaneously by healthy uninitiated volunteers, pressure and a tingling sensation, of which the first develops in a continuous manner. The pattern in which the absolute need develops is described by the terms: no sensation, weak awareness, stronger awareness, weak need, stronger need a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 19 publications
3
51
1
Order By: Relevance
“…Due to the invasiveness, patient risk, and cost of this test, non‐invasive hydration protocols have been developed to characterize real‐time bladder sensation in patients with and without OAB . Some of these studies have used a tablet‐based sensation meter that participants used to track real‐time, unprompted bladder sensation .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the invasiveness, patient risk, and cost of this test, non‐invasive hydration protocols have been developed to characterize real‐time bladder sensation in patients with and without OAB . Some of these studies have used a tablet‐based sensation meter that participants used to track real‐time, unprompted bladder sensation .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately this technique is invasive and fills the bladder retrograde. Recently interactive focus group sessions have been described to study bladder sensations non‐invasively 2. This qualitative research method can be used to explore thoughts from subjects3 and was found to be useful in studying bladder sensations in healthy volunteers and helpful to refine the terminology that was used to describe these sensations.…”
Section: Introductionmentioning
confidence: 99%
“…This qualitative research method can be used to explore thoughts from subjects3 and was found to be useful in studying bladder sensations in healthy volunteers and helpful to refine the terminology that was used to describe these sensations. In order to induce a constant forced diuresis a water loading protocol was used,4 and during bladder filling healthy subjects described the development and characteristics of bladder sensation as either a pressure or tingling sensation 2…”
Section: Introductionmentioning
confidence: 99%
“…ROC curves were calculated for WF and PVR to evaluate potential cut-off values and to test these measures of voiding performance (contraction strength and efficiency) as predictors of symptoms and observations relating to non-obstructive voiding impairment. Based on reports suggesting a continuous, quasi-linear progression of bladder volume vs. reported sensations [13,14], sensory volume thresholds were regarded as ordinal (1 = FS, 2 = FD, 3 = ND, 4 = SD) and plots of volume vs the ordinal scale were prepared for symptoms and observation categories. Linearity of sensory volume threshold and wall stress function plots were checked by Pearson r and POL Scientific UAB, DU and contractility linear regression used to compare slopes and intercepts.…”
Section: Methodsmentioning
confidence: 99%